The Effectiveness of Indoor Socks with Medial Arch Support in Decreasing Pain in Patients with Posterior Tibial Tendon Dysfunction: a Prospective, Double-blinded, Randomized Controlled Trial - K, Kiatbamrungpunt; N, Chadchavalpanichaya (ASEAN Journal of Rehabilitation Medicine, 2020)
Objective: To study the effectiveness in application of indoor socks with medial arch support on decreasing pain in patients with posterior tibial tendon dysfunction Study design: Prospective, randomized single-blinded controlled trial Setting: Foot clinic, Department of Rehabilitation Medicine, Faculty of Medicine Siriraj Hospital Subject: Forty – two patients who had posterior tibial tendon dysfunction with foot pain were enrolled in the prospective, randomized single-blinded controlled trial at the Out - Patient Rehabilitation Medicine Clinic, Siriraj Hospital during August 2017 – August 2018 Methods: Patients were randomized into two groups, the study group (using socks with medial arch support) and the control group (using socks with flat foam). Patients in both groups were advised to wear them while walking and standing indoors for 2 weeks. The complication and duration of using socks with medial arch support or sham were recorded in a logbook. The pain score, as recorded by numeric rating scale, was asked before and after 2 weeks after using them. Results: After using socks for 2 weeks, there were statistically significant decreases in foot pain in both the study group (p-value < 0.001) and in the control group (p-value = 0.004) compared to baseline. However, when comparing the differences in pre / post-intervention foot pain between two groups, there was no statistically significant difference (p-value = 0.07). Conclusion: In patients with posterior tibial tendon dysfunction, using indoor socks with medial arch support showed no statistically significant difference in decreasing foot pain when compared to the control group.